Influência do espaçamento na sobrevivência, frequência por classe de diâmetro e relação hipsométrica altura-diâmetro do Eucalyptus urophylla - Brandi , Renato M; Couto , Laércio; de Paula Neto , Francisco (Revista Ceres, 2025)
This study was carried out to investigate the effects of five interval spacings on survival and growth habit of Eucalyptus urophylla of hybrid origin. Seedlings were grown in containers (torrões paulistas) and planted in the field accorging to a randomized block design with three blocks. Land belonging to the Belgo-Mineira Company in Coronel Fabriciano County, Minas Gerais, Brazil, was used.